Brazil : Report on the Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2005)
This paper presents the report on Brazil's Observance of Standards and Codes on the Financial Action Task Force Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. Brazilian authorities report that the major sources of illegal proceeds are crimes against the financial system, drug trafficking, and tax evasion. Law 9613/98 and sector-specific regulations incorporate the financial supervisors into the regime, and they appear to be broadly ensuring compliance by the financial sector.